If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -12) = 4x Reorder the terms: 8(-12 + x) = 4x (-12 * 8 + x * 8) = 4x (-96 + 8x) = 4x Solving -96 + 8x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -96 + 8x + -4x = 4x + -4x Combine like terms: 8x + -4x = 4x -96 + 4x = 4x + -4x Combine like terms: 4x + -4x = 0 -96 + 4x = 0 Add '96' to each side of the equation. -96 + 96 + 4x = 0 + 96 Combine like terms: -96 + 96 = 0 0 + 4x = 0 + 96 4x = 0 + 96 Combine like terms: 0 + 96 = 96 4x = 96 Divide each side by '4'. x = 24 Simplifying x = 24
| 8x-72=7x-77 | | 2p+18=8p-6 | | 28y+5=21 | | N+18=625 | | 4(x-5)=43-3x | | 8nx=8x | | 7m-18=38 | | 110x+64y=2 | | 8x+5y+3z=15 | | 3x-5/4=12 | | -26+4x=-39+15x | | x^3=48 | | 6x+12=-20-2x | | 9x+28=3x+94 | | 37-3x=12-8x | | 5x(n+2)=3x(n-4) | | 0.8x*(d-0.8x/2) | | 3+8x=3+x | | 5x(n+2)=-3x(n-4) | | y=7E-10x | | 10ab(2c)*3b+d= | | (5x-2y)(5x+2y)= | | -6=v+6-6 | | 2x+21=10x-5 | | 13x+1=11x+1 | | (2n+3)(3n+2)= | | 0.8x*f*b*(d-0.8x/2) | | 3x^2+3y^2+24x-6y+9=0 | | 7x^2-6x+20=0 | | d*(b-0.8x/2) | | Y-b=2(x-4) | | 7+2=7x-3 |